Greigite formed in early Pleistocene lacustrine sediments from the Heqing Basin, southwest China, and its paleoenvironmental implications. (1st May 2018) - Qiang, Xiaoke; Xu, Xinwen; Zhao, Hui; Fu, Chaofeng
Graphical abstract: Highlights: Greigite is the dominant magnetic mineral in the studied ancient lacustrine sediments. Greigite was formed during early diagenesis. Greigite is present in both weak and strong summer monsoon intervals, but is more abundant in the former. The concentration of dissolved iron was the dominant controlling factor for greigite formation. Abstract: The ferrimagnetic iron sulfide greigite (Fe3 S4 ) occurs widely in sulfidic lacustrine and marine sedimentary environments. Knowledge of its formation and persistence is important for both magnetostratigraphic and paleoenvironmental studies. Although the formation mechanism of greigite has been widely demonstrated, the sedimentary environments associated with greigite formation in lakes, especially on relatively long timescales, are poorly understood. A long and continuous sequence of Pleistocene lacustrine sediments was recovered in the Heqing drill core from southwestern China, which provides an outstanding record of continental climate and environment. Integrated magnetic, geochemical, and paleoclimatic analysis of the lacustrine sequence provides an opportunity to improve our understanding of the environmental controls on greigite formation. Rock magnetic and scanning electron microscope analyses of selected samples from the core reveal that greigite is present in the lower part of the core (part 1, 665.8–372.5 m). Greigite occurs throughout this interval and is the dominant magnetic mineral, irrespective of the climatic state. The magnetic susceptibility (χ) record, which is mainly controlled by the concentration of greigite, matches well with variations in the Indian Summer Monsoon (ISM) index and total organic carbon (TOC) content, with no significant time lag. This indicates that the greigite formed during early diagenesis. In greigite-bearing intervals, with the χ increase, Bc value increase and tends to be stable at about 50 mT. Therefore, we suggest that χ values could estimate the variation of greigite concentration approximately in the Heqing core. Greigite favored more abundant in terrigenous-rich and organic-poor layers associated with weak summer monsoon which are characterized by high χ values, high Fe content, high Rb/Sr ratio and low TOC content. Greigite enhancement can be explained by variations in terrigenous inputs. Our studies demonstrate that, not only the greigite formation, but also its concentration changes could be useful for studying climatic and environmental variability in sulfidic environments.